Data from Improving the Affordability of Anticancer Medicines Demands Evidence-Based Policy Solutions - Nora Franzen; Giorgia Romagnoli; Andreas Ziegler; Valesca P. Retèl; Theo J.S. Offerman; Wim H. van Harten (2023)
AbstractThe high cost of many new anticancer medicines significantly impedes breakthrough discoveries from reaching patients. A commonly heard refrain is that high prices are necessary to compensate for the high costs of research and development (R&D). Yet, there are promising policy proposals aimed at improving affordability without compromising innovation. In seeking new policy solutions, we argue for a shift away from entrenched opinion toward an evidence-based discourse that is grounded in experiments and real-world pilot studies. We offer a novel perspective and practical recommendations on how empirical evidence could and should be gathered to inform evidence-based policy interventions that lead to sustainable medicine prices in oncology.See related article by Franzen et al. (Cancer Res Commun 2022;2:39–47).